Kajian Penilaian Keberkesanan Program Perangi Dadah (pdh) Habis-habisan 2017-2018 - Haslee Sharil Lim Abdullah; Farhana Saberi; Lau Poh Li; Nor Azri Ahmad; Sallina Mansur; Nur Faizah Abdul Kahar; Siti Nubailah Mohd Yusof (AADK, 2024)
JILID 13, NO. 1, JUN 2021